Attenuation-based characterization of coronary atherosclerotic plaque: comparison of dual source and dual energy CT with single-source CT and histopathology - Henzler, Thomas; Porubský, Štefan; Kayed, Hany; Harder, Nils; Kriššák, Radko; Meyer, Mathias; Süselbeck, Tim; Marx, Alexander; Michaely, Henrik J. M.; Schoepf, U. J.; Schönberg, Stefan; Fink, Christian (European journal of radiology, 2011)
Objective - To compare different CT acquisition techniques regarding for attenuation-based characterization of coronary atherosclerotic plaques using histopathology as the standard of reference. - Materials and methods - In a post mortem study 17 human hearts were studied with dual-source CT (DSCT) and dual energy CT (DECT) mode on a DSCT as well as with 16-slice single-source CT (SSCT). At autopsy, atherosclerotic lesions were cut at 5μm sections. Histopathologic classification of the plaques according to the American Heart Association (AHA) criteria was performed by two pathologists. Attenuation values of all plaques were measured in DSCT, DECT and SSCT studies, respectively and classified based on attenuation according to modified AHA criteria. - Results - 58 coronary plaques were identified at autopsy. Regardless of the CT technique only 52/58 plaques were found at CT (sensitivity=89.6%). There was no significant difference between the mean attenuation values of different plaque types between DSCT, DECT, and SSCT: type IV: 11HU/8HU/19HU; type Va: 44HU/45HU/52HU; type Vb: 1088HU/966HU/1079HU). The sensitivity for correct classification varied depending on the plaque type (type II=0%, type III=0%, type IV=43%, type Va=58%, Vb=97%). - Conclusion - Independent of the used acquisition technique, SSCT, DSCT and DECT show similar results for attenuation-based characterization of atherosclerotic coronary plaques.